Blood oxygen level with long-term use of N95 face mask in dental practice during the coronavirus pandemic “Covid-19” - Amr Bayoumi; Maha Shawki; Amro Abdulaziz; Mohammed Allam; Mohamed Mosleh (Advances in Medical, Pharmaceutical and Dental Research)
Wearing a mask for a long time, particularly N95, is sometimes uncomfortable, annoying, and confining, making catching breath difficult and reducing the oxygen level in the blood. The study aimed to investigate the change in blood oxygen level when wearing an N95 mask for three hours among dental practitioners in dental clinics and the impact of low O2 levels on the general status of students while working in a stressful environment. Material and methods. The sample included 82 adult healthy senior dental students attending the student oral surgery clinical sessions. All Participants had their oxygen saturation Spo2 measured using a portable pulse oximeter before, 1hour, 2hours, and 3 hours after wearing the mask, and were allowed to describe their feeling of discomfort throughout the study. Systolic and diastolic blood pressure (SBP and DBP), and heart rate (HR) were also measured before and 3 hours after wearing the mask. Results. 84.15% (n= 69) of the participants reported some discomfort affecting their general status and clinical performance. There was a statistically significant increase in mean heart rate after three hours (P-value = 0.001) while there was no statistically significant change in mean systolic/diastolic blood pressure after three hours (P-value = 0.630) and (P-value=0.407) respectively. On the other hand, the mean Oxygen saturation after three hours showed a statistically significantly lower value compared with baseline measurement. Conclusion. This study revealed a decrease in the oxygen saturation (SpO2) and a slight increase in pulse rate compared to baseline values in all students three hours after wearing an N95 face mask. In addition, the N95 mask induced discomfort in breathing, a decrease in physical performance, and increased fatigue not related to prolonged standing and stress.